Prior dispositions and actual behavior in dictator and ultimatum games - Hermann Brandstätter; Werner Güth; Judith Himmelbauer; Willy Kriz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Individuals differ in behavior since neither their ethical constraints, their attitudes towards risk, nor their analytical talents are the same. In an experimental prephase we tried to elicit such differences by confronting participants with suitable one-person-decision problems. In the main phase they played successively the dictator game, the ultimatum game, and finally the combination of the former two, originally studied by Güth and van Damme (1998). A final personality questionnaire elicits self-evaluations concerning ethical constraints, attitude towards risk, and analytic capability in addition to more general personality traits. We mainly investigate the consistency of prior dispositions (inferred from individual decision behavior in the prephase and from the self-reports) and actual behavior (in the main phase).What is reported in this paper is a part of a more complex set of results. The focus here is on the effects of three individual difference variables (benevolence, intelligence, and reciprocity orientation) on behavior in the role of an active player (the giver) and in the role of a passive player (the receiver). Benevolence (as personality trait of the active player) facilitates equity considerations in his/her offers to the powerless, but not to the powerful receiver. Reciprocity orientation makes male (not female) participants in the role of powerful receivers (powerful, because, if they decline the offer, none of the players gets anything) to set higher minimal demands (higher acceptance thresholds). Intelligence had no significant effects on bargaining behavior.
urn:nbn:de:kobv:11-10046418
Keywords: 330